Impactos da política de ICMS ecológico - uma análise qualitativa sob o enfoque do federalismo fiscal - Gonçalves, Juliano Pessanha (2003)
This thesis aims at identifying the main impacts of the policy of ecological valueadded tax (ICMS-E) L1nder the discussions about the fiscal federalismo It focuses on ICMS-E redistributive and compensatory impacts. For my analysis, I used the debate in the growing literature on ICMS-E and a case study of the State of Minas Gerais in the Brazilian Southeast.